A single atom change "switches-on" the solar-to-energy conversion efficiency of Zn-porphyrin based dye sensitized solar cells to 10.5%1. Issue 4 (1st April 2015) - Cabau, Lydia; Vijay Kumar, Challuri; Moncho, Antonio; Clifford, John N.; López, Núria; Palomares, Emilio
<x xml:space="preserve">Abstract</x> In this work we report how crucial is the correct design of the porphyrin sensitizers in Dye Sensitized Solar Cells (DSSCs).